POVERTY AND FAITH AS REFLECTED IN MAJID MAJIDI’S CHILDREN OF HEAVEN - Diyah Fitri Wulandari (Dinamika Bahasa dan Budaya, 2019)
People in the world are facing problem. The problems could be vary, like health, financial, education, poverty etc. In facing the problem, one’s should have a personal shield that can protect him/herself from doing bad deeds. Faith is one of the personal shield. Children of Heaven is a film which tells about main characters’ problem dealing with poverty. This study aimed at analyzing the main characters’ faith in coping problems dealing with poverty. This is a qualitative study. The data in this study were taken from Majid Majidi’s Children of heaven. The result of this study found that faith brings the main role in the main character’s attitude. Ali, and his family shows how they can cope their problems dealing with poverty and the faith as their personal shield. The manifestation of the faith are shown in character’s attitude like patience, obedience to the parents, and honesty.